2016
DOI: 10.5194/gi-5-241-2016
|View full text |Cite
|
Sign up to set email alerts
|

A novel permanent gauge-cam station for surface-flow observations on the Tiber River

Abstract: Abstract. Flow monitoring of riverine environments is crucial for hydrology and hydraulic engineering practice. Besides few experimental implementations, flow gauging relies on local water level and surface-flow velocity measurements through ultrasonic meters and radars. In this paper, we describe a novel permanent gauge-cam station for large-scale and continuous observation of surface flows, based on remote acquisition and calibration of video data. Located on the Tiber River, in the center of Rome, Italy, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…The performance of PIV in this study is consistent with the previous studies that exploited LSPIV for flow analysis [24]. Previous research has shown that LSPIV based on standard FFT correlation or DCC is prone to underestimating flow velocities due to insufficient seeding density [48,49,63,64]. Our results have also indicated that independent on the correlation method employed, LSPIV tends to underestimate flow velocities; however, the use of ensemble correlation that averages correlation matrices before determining the correlation peak, in many cases reduces the magnitude of differences between the reference velocities and the PIV values.…”
Section: Discussionsupporting
confidence: 89%
“…The performance of PIV in this study is consistent with the previous studies that exploited LSPIV for flow analysis [24]. Previous research has shown that LSPIV based on standard FFT correlation or DCC is prone to underestimating flow velocities due to insufficient seeding density [48,49,63,64]. Our results have also indicated that independent on the correlation method employed, LSPIV tends to underestimate flow velocities; however, the use of ensemble correlation that averages correlation matrices before determining the correlation peak, in many cases reduces the magnitude of differences between the reference velocities and the PIV values.…”
Section: Discussionsupporting
confidence: 89%
“…A video recorded at the gauge-cam station on the Tiber River underneath the bridge "Ponte del Foro Italico" in the city of Rome, Italy [52,53], on February 2015, at 7:40 a.m., was analyzed through OTV, Figure 1c. The gauge-cam station acquires one-minute long videos every ten minutes through a Mobotix FlexMount S15 weatherproof internet protocol camera.…”
Section: A Moderate Flood Event In the Tiber Rivermentioning
confidence: 99%
“…Conventional methods may be used to monitor flash floods in wadi systems, for instance, the measuring of water levels and the slope-area method to generate water level-discharge relationships (rating curves). However, the field measurements and observations for peak discharge values have a limited range for establishing accurate rating curves [6]. Moreover, the slope-area method in wadi systems relies on flood marks from post-flood surveys, for example, floating debris and sediments deposited on both banks of the channel, to obtain the water surface slope in each cross-sectional area, which affects the reliability of discharge predictions.…”
Section: Introductionmentioning
confidence: 99%
“…The LSPIV technique is among the most commonly investigated type of flash flood monitoring systems, and several studies of image-based methods have been undertaken in riverine systems [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%